2020
DOI: 10.1504/mejm.2020.105228
|View full text |Cite
|
Sign up to set email alerts
|

Linking elements of entrepreneurial orientation and firm performance: examining the moderation of environmental dynamism

Abstract: This research is designed to examine the impact of elements of entrepreneurial orientation (EO) on firm performance by considering environmental dynamism as a potential moderator. Data was gathered from 143 textile and leather manufacturing small and medium-sized enterprises (SMEs) in Pakistan. Partial least square (PLS) was employed to analyse the hypotheses. The findings reveal that EO elements positively affect firm performance directly, except in the case of proactiveness. However, the nexus between the el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 55 publications
(75 reference statements)
2
5
0
Order By: Relevance
“…More preciously, the theory suggested that competitive advantage can be sustained, especially through internal organizational capabilities (Anwar & Shah, 2021). Hence, the empirical study is consistent with past entrepreneurial literature, that EO (innovativeness, proactiveness, and risk-taking) can significantly enhance the firm performance as elicited through the resource-based view theory (Shafique & Saeed, 2020;Shen et al, 2020). The central principle of RBV is that idiosyncratic organizational resources are the key factors for sustained competitive advantage, while EO is a part of one of these unique resources.…”
Section: Entrepreneurial Orientation and Sustainable Competitive Perf...supporting
confidence: 84%
See 1 more Smart Citation
“…More preciously, the theory suggested that competitive advantage can be sustained, especially through internal organizational capabilities (Anwar & Shah, 2021). Hence, the empirical study is consistent with past entrepreneurial literature, that EO (innovativeness, proactiveness, and risk-taking) can significantly enhance the firm performance as elicited through the resource-based view theory (Shafique & Saeed, 2020;Shen et al, 2020). The central principle of RBV is that idiosyncratic organizational resources are the key factors for sustained competitive advantage, while EO is a part of one of these unique resources.…”
Section: Entrepreneurial Orientation and Sustainable Competitive Perf...supporting
confidence: 84%
“…Organizations undertake to conceptualize new products and services as per the customer demands and to fulfill the customer demands, businesses adopting innovation, taking a risk, and pioneer ability to gain opportunity and enhance performance (Majid et al, 2019). Organizations can adopt strategic orientation (entrepreneurial and market) due to external market uncertainty (Shafique & Saeed, 2020). To stabilize their position and sustain competitive performance, organizations need to innovate new things compared to competitors (Majid et al, 2020).…”
Section: The Mediating Role Of Strategic Flexibility Between Entrepre...mentioning
confidence: 99%
“…It is also found that there is a positive and important link between culture and how well new products are made, and that innovation and product performance vary between technology firms. In a similar way, the study by Shafique and Saeed (2020) shows that firms can use differences in innovative and environmentally friendly practises to gain a competitive edge. There are different ways that a company can use green practises that help the environment and people (Khan et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 85%
“…Similarly, other Similar moderators and mediators can be tested in future studies to unleash prominence implications. For instance, Shafique and Saeed (2020) tested the moderating role of environmental dynamism between EO and performance, thereby opening a door for future researchers to test environmental factors (government pressure, sustainability reporting and market uncertainty) that might give useful information for policy implications.…”
Section: Implications For Practicementioning
confidence: 99%